Blended digital health intervention for adolescents at high risk with digital media use disorders: protocol for a randomised controlled trial within the Res@t-Consortium - Oliver Labrenz; Oliver Labrenz; Lucie Waedel; Lucie Waedel; Michael Kölch; Michael Kölch; Susanne Lezius; Christina Wacker; Antonia Fröhlich; Antonia Fröhlich; Kerstin Paschke; Rainer Thomasius; et al. (Frontiers in Psychiatry)
BackgroundDigital media use disorder (DMUD) is a prevalent problem among young people, which can result in adverse consequences and functional impairments across multiple domains of life due to a persistent inability to regulate one’s use, which can lead to the development of psychological problems. In particular, children and adolescents who live in families that are part of the child and youth welfare system and receive support services are considered to be at high risk of developing mental disorders. It is less likely that these families will choose a therapeutic setting for the treatment of DMUD. The objective is to reduce DMUD-related symptoms and improve media use behaviour through the implementation of an app-based training programme.MethodsThe efficacy of Res@t digital, initially conceived as an adjunct to child and adolescent psychiatric treatment, is to be evaluated for n= 32 children and adolescents with a media use disorder or at risk of developing this disorder, and their families enrolled in child and youth welfare services. The efficacy of the app will be evaluated in a randomised controlled trial with a waitlist control group. The primary outcome is the reduction of DMUD symptoms over a 20-week period following the onset of app training. Secondary outcomes include EEG measurements and changes in standardised psychopathological variables.DiscussionShould the Res@t app prove efficacious when compared to a waitlist control group, it would constitute an evidence-based intervention for the treatment of DMUD in children and adolescents. For high-risk families, the app could serve as a motivational tool to prompt action regarding potential DMUD and facilitates access to therapeutic facilities.Clinical trial registrationhttps://drks.de, identifier DRKS00033379.